Coordination of counter-terrorism actors, whose activities are directed by the Ministry of Internal Affairs of Ukraine within its powers (Law and Safety, 2024)
Currently, Ukraine has been constantly struggling with hybrid threats, especially terrorism, which arose as a result of the Russian Federation’s aggression. The problematic issue of organising and counteracting such a phenomenon as a terrorist act requires special attention, as the inability of key public authorities responsible for detecting and suppressing these criminal acts to apply organisational and managerial decisions correctly does not allow minimising them. Therefore, there is no doubt that the effectiveness of countering such threats depends on the activities of the Interagency Coordination Commission of the Anti-Terrorist Centre of the Security Service of Ukraine, which, for its part, regulates the conduct of measures to identify and eliminate the causes and conditions of terrorist acts and other crimes committed for terrorist purposes, since the tactics of combating this crime are formed, in particular, by conducting certain activities by officers of the National Police of Ukraine, the National Guard of Ukraine, the State Border Guard Service of Ukraine, and the State Border Guard Service of Ukraine. These bodies are interdependent in fulfilling their tasks in the fight against terrorism, which has recently been spreading across the entire territory of our country and leaving traces in the form of destroyed infrastructure and civilian deaths. The latest ideas on the development of organisational and managerial measures, including special operations or measures aimed at the rapid termination of terrorist acts, play a priority role. The article examines the gaps in the legislation and proposes to consider amending it. Such amendments will help to increase the level of coordination of counter-terrorism actors, which are part of the Interagency Coordination Commission of the Anti-Terrorist Centre under the Security Service of Ukraine and whose activities are directed by the Minister of Internal Affairs of Ukraine, in order to improve the prevention of terrorist activities, their detection, suppression and minimisation of their consequences. A properly constructed model can be used in the future and demonstrate a high and positive result in countering terrorism in Ukraine.
Keywords: public authorities; counter-terrorism; terrorist act; Interagency Coordination Commission of the Anti-Terrorist Centre at the Security Service of Ukraine; national system of counter-terrorism.